The Handling of Linen Needs in the Context of Cleanliness, Health, Safety, and Environment Sustainability - Zainal Hasan; Ni Luh Eka Armoni; I Wayan Basi Arjana; Ni Nyoman Triyuni; Kanah; Wahyuning Dyah (The Postgraduate School of Tourism Sahid Polytechnic, 2022)
ABSTRACT Purpose: The purpose of this study was to analyze the needs and the handling of room linen at a five-star hotel located in Nusa Dua area, Bali, Indonesia, in the context of CHSE (cleanliness, health, safety, and environment sustainability). Research methods: The method used in this research is a qualitative method using descriptive data both in writing and orally from respondents through field observations, interviews, and documentation. Results and discussion: The housekeeping department's linen management system at the hotel has not met linen management standards. The availability of existing Linen with a theoretical method of at least 3 par stocks was found to be lacking in the number of linen and the way the linen was handled was still not in accordance with existing procedures. Implication: Handling of room linen needs to be improved to get optimal results and it is necessary to increase the number of linens so that hotel operations can run more effectively and efficiently and do not force linen that is no longer suitable for use to be reused. Keywords: linen, par stock, CHSE, hotel.